A Homozygous CASQ2 Mutation in a Japanese Patient with Catecholaminergic Polymorphic Ventricular Tachycardia - Fujisawa, Taishi (Case Rep Genet, 2019)
A 62-year-old female had suffered from recurrent syncopal episodes triggered by physical and emotional stress since childhood. She had no family history of sudden death. An intensive examination could not detect any structural disease, and exercise stress testing provoked polymorphic ventricular ectopy followed by polymorphic ventricular tachycardia accompanied with syncope leading to a diagnosis of catecholaminergic polymorphic ventricular tachycardia (CPVT). A genetic analysis with a next generation sequencer identified a homozygous W361X mutation in the CASQ2 gene. Careful history taking disclosed that her parents had a consanguineous marriage. Here we present a Japanese patient with a recessive form of CPVT.